Affirmation, validation, and empowerment: Influences of a composition competition on students' self-concepts as musicians. (June 2017) - Albert, Daniel J.
The purpose of this study was to determine if participation in a composition competition influenced four K–12 students' self-concepts as musicians. Research questions explored motivations for these four students to enter into a composition competition, influences of the competition on students' self-concepts as musicians (if at all), and effects of the competition besides those of self-concept as a musician (if at all). Data sources for this multiple case design study included semi-structured interviews, journals, and wiki interactions. Findings determined that acceptance to the competition, performance of students' works, and the reception that students received validated and strengthened their self-concepts as musicians. Suggestions for teaching practice include providing constructive feedback from competition adjudicators, creating face-to-face and online experiences for student composers to network, and offering non-adjudicated composition festival experiences for students.